Pengaruh Model Project Based Learning Dalam Melatih Kemampuan Argumentasi Peserta Didik - Dewi Nurdiyanti; Dewiantika Azizah; Anita Fatimatuzzahra (Postgraduate, University of Mataram, 2024)
The preliminary study data shows that the argumentation ability in SMA 8 Kota Cirebon is relatively low, this shows that the argumentation ability of students has not been stimulated properly. The Project Based Learning model is here to train students' argumentation ability. Using an experimental method with Quasi Experimental Design. The sample of this study was the control and experimental classes. The assessment technique was in the form of observation sheets and t-tests. The results of the study showed that the project based learning model can train argumentation ability through its syntax, t-test and n-gain test there were significant values ​​with t-test results of 0.05 <0.01 while in the n-gain test with a result of 67.25% with a fairly effective category, so that argumentation ability is at level 3. The conclusion that can be drawn from the application of this project based learning model can train argumentation ability.